Shared value: agricultural carbon insetting for sustainable, climate-smart supply chains and better rural livelihoods - Banerjee, A; Rahn, Eric; Läderach, Peter R.D.; Hoek, Rein van der (2013)
The relentless advance of climate change negatively impacts farmers, businesses, and consumers by putting greater pressure on natural resources, making the weather more unpredictable, and depressing crop productivity. To cope with climate change requires multilateral efforts that draw on the experience of farmer groups, research and development organizations, and the private sector. One increasingly important focal point for such efforts is an approach referred to as carbon insetting, which offers the private sector a means to create shared value for the benefit of all stakeholders. The approach can make a company’s value chain more productive and resilient, sustaining supplies over the long term. By creating synergies between climate change mitigation and adaptation in agriculture (e.g., through practices such as agroforestry), carbon insetting can also generate incentives and funding for climate change adaptation while enhancing farmers’ livelihoods.